Molybdenum isotope fractionation in soils: Influence of redox conditions, organic matter, and atmospheric inputs. (1st August 2015) - Siebert, C.; Pett-Ridge, J.C.; Opfergelt, S.; Guicharnaud, R.A.; Halliday, A.N.; Burton, K.W.
Abstract: Molybdenum isotope fractionation accompanying soil development is studied across three pedogenic gradients encompassing a range of controlling factors. These factors include variable redox conditions, organic matter content, Fe and Mn oxy(hydr)oxide content, mineral composition, degree of weathering, pH, type and amount of atmospheric inputs, age, climate, and underlying rock type. Soil profiles from the island of Maui (Hawaii) along a precipitation gradient ranging from 850 to 5050 mm mean annual precipitation show a decrease in average soil δ 98 Mo from −0.04 ± 0.11‰ at the driest, most oxic site, which is indistinguishable from the basalt parent material (−0.09 ± 0.08‰), to −0.33 ± 0.10‰ at the wettest, most reducing site. A suite of 6 Icelandic soils display a broad trend with heavier δ 98 Mo values (up to +1.50 ± 0.09‰) in soil horizons that are more weathered and have higher organic matter content. Selective extractions of Mo from different soil components indicate that the association with organic matter and silicate or Ti-oxide residue dominates retention of Mo in these soils, with adsorption on Fe and Mn oxy(hydr)oxides playing a lesser role. Across all basaltic soils, δ 98 Mo values are lighter in soils that exhibit the most net Mo loss relative to the parent material, and δ 98 Mo values are heavier in soils that exhibit net Mo gains. A well-drained regolith profile in the Luquillo Mountains of Puerto Rico developed on quartz diorite shows heavier δ 98 Mo values than the parent material (up to +0.71 ± 0.10‰ with an integrated profile average of +0.28 ± 0.10‰) in soil and shallower saprolite, despite overall moderate loss of 28% of Mo relative to the bedrock. However, the deeper saprolite is unfractionated from bedrock (−0.01 ± 0.10‰, quartz diorite bedrock) indicating that rock weathering dissolution processes and secondary clay formation do not fractionate Mo isotopes. Our data suggest that the Mo mass balance and isotope composition of soils are controlled by redox conditions, organic matter, and atmospheric inputs. In this way Mo isotopes have the potential to react to and record climate driven changes in the weathering environment. The presence of both isotopically light and heavy Mo (relative to parent material) across all sites and within individual soil profiles suggests that it is normal for multiple fractionation mechanisms to operate under the open-system conditions of soils.